Bulk crystal growth, characterization and thermodynamic analysis of aluminum nitride and related nitrides - Du, Li (Kansas State University, 2011)
The sublimation recondensation crystal growth of aluminum nitride, titanium nitride, and yttrium nitride were explored experimentally and theoretically. Single crystals of these nitrides are potentially suitable as substrates for AlGaInN epitaxial layers, which are employed in ultraviolet optoelectronics including UV light-emitting diodes and laser diodes, and high power high frequency electronic device applications. A thermodynamic analysis was applied to the sublimation crystal growth of aluminum nitride to predict impurities transport (oxygen, carbon, and hydrogen) and to study the aspects of impurities incorporation for different growth conditions. A source purification procedure was established to minimize the impurity concentration and avoid degradation of the crystal’s properties. More than 98% of the oxygen, 99.9% of hydrogen and 90% of carbon originally in the source was removed. The AlN crystal growth process was explored in two ways: self-seeded growth with spontaneous nucleation directly on the crucible lid or foil, and seeded growth on SiC and AlN. The oxygen concentration was 2 ~ 4 x 1018cm-3, as measured by secondary ion mass spectroscopy in the crystals produced by self-seeded growth. Crystals grown from AlN seeds have visible grain size expansion. The initial AlN growth on SiC at a low temperature range (1400°C ~1600°C) was examined to understand the factors controlling nucleation. Crystals were obtained from c-plane on-axis and off-axis, Si-face and C-face, as well as m-plane SiC seeds. In all cases, crystal growth was fastest perpendicular to the c-axis. The growth rate dependence on temperature and pressure was determined for TiN and YN crystals, and their activation energies were 775.8±29.8kJ/mol and 467.1±21.7kJ/mol respectively. The orientation relationship of TiN (001)

W (001) with TiN [100]

W [110], a 45o angle between TiN [100] and W [100], was seen for TiN crystals deposited on both (001) textured tungsten and randomly orientated tungsten. Xray diffraction confirmed that the YN crystals were rock-salt structure, with a lattice constant of 4.88Å. Cubic yttria was detected in YN sample from the oxidation upon its exposed to air for limited time by XRD, while non-cubic yttria was detected in YN sample for exposures more than one hour by Raman spectra.
Keywords: Bulk Crystal Growth; Thermodynamic Analysis; Aluminum Nitride; Transition Metal Nitrides; Chemical Engineering (0542); Materials Science (0794)